Magi : the labyrinth of magic. 37 - Otaka, Shinobu; Werry, John (Translator) (VIZ Media, LLC, 2019)
"The world teeters on the edge of destruction as Alibaba squares off against former comrades who are convinced that everything and everyone should return to their basic Rukh forms. In the Sacred Palace, David and Sinbad clash. Only a power beyond Maximum Magic can decide this battle for the ultimate fate of the world!"--Page [4] of cover.